The Effect of Sales Growth, Firm Size, and Dividend Policy on Firm Value: A Study of Energy Sector Companies Listed on The Indonesia Stock Exchange for the 2019–2023 Period - Muhammad Fayyadh; Galuh Tresna Murti (SAFE-Network, 2026)
This study aims to examine in greater depth the effect of sales growth, dividend policy, and firm size on firm value in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Employing a quantitative method with panel data regression, the study uses purposive sampling to select 11 energy companies, resulting in 55 observations derived from audited annual reports and official IDX publications. Data analysis includes descriptive statistics, classical assumption tests, and model selection using the Chow Test, Hausman Test, and Lagrange Multiplier Test, followed by hypothesis testing through F-test and t-test using EViews 13 software. The findings reveal that the three independent variables jointly exert a significant influence on firm value, yet only firm size shows a significant negative partial effect, while sales growth and dividend policy do not demonstrate significant impacts. This finding confirms that in the energy sector, large companies do not always receive higher market valuations, making asset management efficiency and business strategy strengthening crucial factors.